CBIO-26. A NEW MODEL OF THE GABP-TERT REGULATORY AXIS IN MAINTAINING IMMORTALITY OF TERT PROMOTER MUTANT TUMOR CELLS. (12th November 2021) - Stevers, Nicholas; Barger, Carter; Lenzo, Olivia; Hong, Chibo; McKinney, Andrew; Costello, Joseph
Abstract: Tumor cell immortality is a fundamental hallmark of human cancers. Normally silenced during somatic cell differentiation, 90% of human tumors reactivate Telomerase Reverse Transcriptase ( TERT ) expression to achieve cellular immortality. TERT, the catalytic subunit of telomerase, complexes with the RNA template molecule TERC to maintain telomeres. Mutations in the TERT promoter ( TERT p) are the most common non-coding mutation across all cancer types and the most frequent mutation within many cancers, such as IDH wildtype glioblastoma (GBM), Melanoma, and Bladder Cancer. TERT p mutations generate de novo E26 Transformation Specific (ETS) binding motifs that are spaced full helical turns from TERT p native ETS sites. Together the de novo and native ETS motifs specifically recruit the GABP tetrameric complex but not the GABP dimer. CRISPR-cas9 mediated insertion/deletion mutagenesis of the unique exon of GABP tetramer forming subunit, GABPB1L (B1L), reduces TERT transcriptional activity in a TERT promoter-mutation dependent manner. Here we show that GABPB1S (B1S), the GABP dimer restricted alternative isoform of GABPB1, is consistently and significantly increased following B1L reduction, a process we have determined to be driven by a conserved homeostatic mechanism whereby the GABP tetramer suppresses expression of one of its own components, GABPB1 . In contrast to the native setting, in the absence of B1L the elevated B1S expression leads to dimer binding to the mutant TERT p and maintenance of TERT expression. Indeed, co-targeting B1L and B1S together, but not B1L alone, via CRISPR-cas9 knockout resulted in a near complete elimination of GABP recruitment to the TERT p and TERT expression, and lead to tumor cell death and eventual senescence in a telomere length dependent manner. Together, this data suggests a new model of the TERT-GABP axis involving the tetramer and dimer and highlights a new and potentially more potent therapeutic strategy to eliminate TERT expression and reverse tumor cell immortality.